Respuesta :

Step-by-step explanation:

[tex] {x}^{2} - 2x + 3 = 0 \\ adding \: 1 \: both \: sides \\ {x}^{2} - 2x + 4 = 1 \\ (x - 2)^{2} = 1 \\ x - 2= \pm \: 1 \\ x = \pm1 + 2 \\ x = 1 + 2 \: \: or \: \: x = - 1 + 2 \\ x = 3 \: \: or \: \: x = 1 \\ \implies \\ \alpha = 3 \: \: \: and \: \: \: \beta = 1\\ \\ \therefore \: { \alpha }^{4} + { \beta }^{4} \\ = {3}^{4} + {1}^{4} \\ = 81 + 1 \\ = 82 \\ \huge\red{ \boxed{\therefore \: { \alpha }^{4} + { \beta }^{4} = 82}}[/tex]

Answer:

Step-by-step explanation:

hello:

here is an solution

Ver imagen ghanami
ACCESS MORE